VISUAL CONTENT STRATEGIES FOR INCREASING ONLINE VISIBILITY OF CULINARY MSMEs - Kiki Putri Amelia (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
Culinary Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic development and cultural preservation but continue to face barriers in achieving online visibility due to limited resources, insufficient digital literacy, and competition with larger firms. This study explores how visual content strategies can enhance the digital presence of culinary MSMEs by employing a qualitative research design involving semi-structured interviews and focus group discussions with 20 culinary entrepreneurs in urban areas, with data analyzed through thematic analysis using NVivo software. The findings highlight three key practices—high-quality images and videos, visual storytelling, and user-generated content (UGC)—which collectively increase engagement, strengthen brand recognition, and foster consumer trust. Case studies demonstrate tangible outcomes, such as a 150% rise in social media followers and significant growth in online sales, while challenges related to financial and technical constraints remain evident. The research critically argues that visual content should be viewed as a strategic necessity rather than an optional tool, urging MSMEs to integrate professional visuals, consumer co-creation, and influencer collaborations to achieve sustainable growth. Moreover, it emphasizes the need for future research to examine long-term impacts on brand equity and cross-cultural contexts, thereby contributing to both academic scholarship and practical guidance in digital marketing for culinary MSMEs.